2006
DOI: 10.2500/ajr.2006.20.2882
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Nasal Resonance after Functional Endoscopic Sinus Surgery

Abstract: This study showed that the FESS effectively increased nasalance scores and nasal volumes in patients with chronic rhinosinusitis, but the increase in nasalance scores did not appear to be achieved largely through the increased nasal volumes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
42
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(44 citation statements)
references
References 5 publications
1
42
1
Order By: Relevance
“…Patients who underwent ESS showed improvement in the perception of their own voice, as reflected in VHI-10 scores, and in nasal resonance. Patients who underwent ESS due to chronic sinusitis and/or nasal polyposis showed a correlation between the increase of the volume of the nasal cavity and the increase of the nasalance score [16]. However, in our study, no correlation was found between the VHI-10 score and the objective measurements.…”
Section: Discussioncontrasting
confidence: 54%
“…Patients who underwent ESS showed improvement in the perception of their own voice, as reflected in VHI-10 scores, and in nasal resonance. Patients who underwent ESS due to chronic sinusitis and/or nasal polyposis showed a correlation between the increase of the volume of the nasal cavity and the increase of the nasalance score [16]. However, in our study, no correlation was found between the VHI-10 score and the objective measurements.…”
Section: Discussioncontrasting
confidence: 54%
“…Several studies have reported voice changes after sinonasal surgery. In one study, the nasalance score significantly increased after sinus surgery . In another report, sinonasal surgery changed the acoustic characteristics of the vocal tract and produced a significant increase in nasality in the early phase …”
Section: Discussionmentioning
confidence: 94%
“…In one study, the nasalance score significantly increased after sinus surgery. 17,18 In another report, sinonasal surgery changed the acoustic characteristics of the vocal tract and produced a significant increase in nasality in the early phase. 19 Although there are no published works concerning EETSA and its impact on acoustic features of the voice, patients in our clinical practice often complained of hypernasality after the EETSA operation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…29 It has been utilized in broad clinical and research applications in speakers with cleft lip and palate and other velopharyngeal impairments. 33,34 Thus, nasalance is considered a robust instrumental measurement in the assessment of resonance disorders. 35,36 If CPP is to be used to report outcome after voice therapy and laryngeal surgeries, it is important to know how different vocal tract configurations would affect it.…”
Section: Introductionmentioning
confidence: 99%